Teaching How to Research: A Case Study on Chemical and Industrial Engineering Degrees - Sergio Nogales-Delgado; José María Encinar Martín; Silvia Román Suero (MDPI AG, 2022)
Final Degree Projects (FDPs) in scientific and technical studies are often the first significant approach to real research and can be a challenging step for students. Their own experience at this stage can influence the students' professional calling to a research career instead of other technical occupations. In any case, it should be an interesting experience for students, regardless of their future career. Thus, suitable guiding by academic tutors is vital to favor the engagement for scientific research as a feasible professional career in youngsters. The aim of this work was to point out our own experience when it comes to teaching how to research, inspired by research-based learning. In other words, this is an example about how to introduce final degree students to research, to prepare them for a possible future career in the research world. Specifically, the expectation for each FDP was to materialize their work in the publication of a research paper or a conference communication, in the context of research carried out in the frame of a transference project with a firm purpose: to emphasize how their work will be applied as a solution to a real problem. To achieve this goal, a general didactic guide (which should be customized for each student) is presented, adapted to a chemical engineering laboratory, mainly devoted to biodiesel and biolubricant production.